Comparing empathy in medical students of two Portuguese medicine schools - Santiago, Luiz Miguel de Mendonça Soares (2020)
Background Empathy is paramount in the doctor-patient relationship being a comprehensive and multidimensional concept. Self-ratings of empathy change across the years of medical education only when the Jefferson Scale of Physicians Empathy is used, with a worrying decrease being found throughout the years in Medicine Schools. As there are only few studies on the factors influencing medical student’s empathy, particularly of the curricular model, this study aimed to compare the levels of empathy of medicine students of two Schools with different curricular models in central Portugal, the Faculty of Medicine - University of Coimbra (FMUC) and the Faculty of Health Sciences - University of Beira Interior (FCS-UBI). Methods Cross-sectional observational study with the Jefferson Scale of Physician Empathy – students’ Portuguese version (JSPE – spv) to 1st, 3rd and 6th year students of the 2017/2018 academic year with descriptive and inferential statistical analysis (p < 0.05). Results Size representative sample of 795 students. Higher total empathy score (TES) (p = 0.008) and “Perspective taking” (p = 0.001) in FCS-UBI were found. JSPE-TES was higher in FCS-UBI, 3rd year (p = 0.038). Higher FCS-UBI “Perspective taking” in the 1st year (p = 0.030) and 6th year (p = 0.044), for “Compassionate care” in the 3rd (p = 0.019) and for “Standing in the patient’s shoes” in the 1st year (p = 0.018) and in FMUC for “Compassionate care” in the 1st year (p = 0.037) and the “Standing in the patient’s shoes” in year 3 (p = 0.002) were found. Higher levels of empathy were found in FCS-UBI female students, for JSPE-TES (p = 0.045) and “Perspective taking” (p = 0.001). Conclusion Higher empathy levels in FCS-UBI were found, with different results in the third year suggesting influence of the medical course teaching characteristics between the two Medicine schools, student’s empathy levels being higher when earlier and more intense contact with patients accompanied by skilled tutors was developed.